2010
DOI: 10.1101/gr.106849.110
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA, mRNA, and protein expression link development and aging in human and macaque brain

Abstract: Changes in gene expression levels determine differentiation of tissues involved in development and are associated with functional decline in aging. Although development is tightly regulated, the transition between development and aging, as well as regulation of post-developmental changes, are not well understood. Here, we measured messenger RNA (mRNA), microRNA (miRNA), and protein expression in the prefrontal cortex of humans and rhesus macaques over the species' life spans. We find that few gene expression c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
345
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(369 citation statements)
references
References 65 publications
18
345
0
Order By: Relevance
“…We analysed data from seven, published, microarray‐based studies of age‐related changes in RNA expression (Barnes et al, 2011; Berchtold et al, 2008; Colantuoni et al, 2011; Kang et al, 2011; Lu et al, 2004; Maycox et al, 2009; Somel et al, 2010, 2011 ). The data came from 22 different brain regions, and the ages of the donors ranged from 20 to 106 years (Figure 1a and Supporting Information Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…We analysed data from seven, published, microarray‐based studies of age‐related changes in RNA expression (Barnes et al, 2011; Berchtold et al, 2008; Colantuoni et al, 2011; Kang et al, 2011; Lu et al, 2004; Maycox et al, 2009; Somel et al, 2010, 2011 ). The data came from 22 different brain regions, and the ages of the donors ranged from 20 to 106 years (Figure 1a and Supporting Information Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…In the human superior frontal gyrus, 30 the highest levels of svtRNA2-1a were detected at early postnatal developmental stages. After the first year, the amount of svtRNA2-1a decreased with low levels being detected at the oldest ages examined.…”
Section: Discussionmentioning
confidence: 99%
“…30 We found that both the major and minor strands reach in rat/mouse was used for control IP. Total RNA was isolated from the Ago2 and control IPs in three independent experiments and the expression of svtRNA2-1a and miR-16 (used as a positive control) was assessed by rRT-PCR Taqman assays.…”
Section: Svtrna2-a Is Upregulated At Advanced Stages Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…This level of expression placed miR-1839-5p into the top 100 most highly expressed miRNAs in the hippocampus, suggesting it is likely to play an important functional role in this tissue. To identify if the high level of expression of miR-1839-5p is conserved in humans, we examined a recently published human prefrontal cortex deep sequencing data set (Somel et al 2010). Indeed, miR-1839-5p expression was in the top 50 miRNAs in all 12 individuals, ranking between the 22nd and 38th most highly expressed ( Fig.…”
Section: Identification Of Novel Mirtrons In the Mouse Brainmentioning
confidence: 99%